Reference Architectures to Measure Data Completeness Across Integrated Databases - Nurul A., Emran; Ahmad, N. (Springer-Verlag Berlin Heidelberg, 2013)
Completeness is an important aspect of data quality and to determine data acceptability one needs to measure the completeness of the data set of concerned. One type of data completeness measure is population-based completeness (PBC). Nevertheless, the notion of PBC will be of little use until we can determine the eorts required (in terms of architectural design) to implement PBC. In this paper, we present the types of PBC system reference architecture and motivate the selection of each.